Cannabinoid Receptor 2 Protects against Acute Experimental Sepsis in Mice - Gui, Huan (Hindawi Publishing Corporation, 2013)
The systemic inflammatory response syndrome can be self-limited or can progress to severe sepsis and septic shock. Despite significant advances in the understanding of the molecular and cellular mechanisms of septic shock, it is still one of the most frequent and serious problems confronting clinicians in the treatments. And the effects of cannabinoid receptor 2 (CB2R) on the sepsis still remain undefined. The present study was aimed to explore the role and mechanism of CB2R in acute sepsis model of mice. Here, we found that mice were more vulnerable for lipopolysaccharide- (LPS-) induced death and inflammation after CB2R deletion (CB2R(−/−)). CB2R agonist, GW405833, could significantly extend the survival rate and decrease serum proinflammatory cytokines in LPS-treated mice. GW405833 dose-dependently inhibits proinflammatory cytokines release in splenocytes and peritoneal macrophages as well as splenocytes proliferation, and these effects were partly abolished in CB2R(−/−) splenocytes but completely abolished in CB2R(−/−) peritoneal macrophages. Further studies showed that GW405833 inhibits LPS-induced phosphorylation of ERK1/2 and STAT3 and blocks IκBα degradation and NF-κB p65 nuclear translocation in macrophages. All data together showed that CB2R provides a protection and is a potential therapeutic target for the sepsis.